Pengaruh Jumlah Produksi, Harga, dan Kurs Dollar AS Terhadap Ekspor Manggis Indonesia - Estiani, Komang; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Mangosteen is one commodities most important in the export of fresh fruit indonesia, because mangosteen is a commodity which unique and economically valuable high. The purpose of influence of both simultaneously and partially between volume production, price, and the US dollar exchange rate against the export of mangosteen Indonesia's to the united states, and this research is to find out the amount of the purpose of a variable production, price, and the US dollar exchange rate of the most dominant influence on the exports of Indonesia mangosteen. In this research using secondary data from years 2000-2013. Data analysis technique to research was used in the linear regression analysis double. The analysis of the data shows simultaneously the amount of volume production, price, and exchange rate usd significant against mangosteen export indonesia of 2000-2013. Partial variables in the number of production and the price of influential positive significant against indonesia exports mangosteen years 2000-2013. The dollar exchange rate variables united states has no significant impact on the export of mangosteen Indonesia of 2000-2013. Then, variable most dominant impact on exports mangosteen Indonesia of 2000-2013 is variable the volume of production.
Keywords: export mangosteen; production; prices; exchange rate US dollar